Implementasi Manajemen Berbasis Kinerja dalam Pengelolaan Sistem Pendidikan yang Bermutu - Hesti Kusumaningrum; Nurhaida Hafni; Maura Karisma Tiar (Al-Faiza : Journal of Islamic Education Studies, 2024)
Management are widely recognized in Indonesia, particularly in the fields of education, social work, and government. Management is a crucial discipline that plays a vital role in enhancing the performance of an organization. Kinerja, or work performance, is a combination of skills, effort, and effort that can be measured. It is a vital aspect of a school's functioning and is closely related to organizational needs, management, and employees. Kinerja management is a comprehensive approach to improving a school's educational system. It involves strategic planning, enhancing instructional practices, and improving student performance. This approach is based on three critical pillars: the teacher, school, and the educational system. The teacher's role in managing kinerja involves collaboration and identifying effective teaching strategies. The school's role in managing kinerja involves promoting teacher development, ensuring student performance, and conducting evaluations. Management are essential components of a school's success. They help create a conducive environment for learning and development, ultimately leading to better student performance.